Tessellation of Chiral-Nematic Cellulose Nanocrystal Films by Microtemplating - Tardy, Blaise L.; Mattos, Bruno D.; Greca, Luiz G.; Kämäräinen, Tero; Klockars, Konrad W.; Rojas, Orlando J. (Advanced Functional Materials, 2019)
In biological architectures, material properties are optimized by the hierarchical structuring of components with a multiscaled order, from the nano- to the macroscales. Such designs enable, for instance, programmed yield points that maximize toughness. However, research efforts in biomimetic materials have focused on the assembly of nano- or macrostructures individually. In this study, high strength cellulose nanocrystals (CNCs), assembled into chiral-nematically ordered structures, are tiled into a higher level, macro-sized, architecture by topographical templating. As templates, two meshed architectures with distinct feature sizes are evaluated, and the optomechanical properties of the resulting films are compared to featureless, flat, CNC films. Controlling capillary stresses arising during CNC assembly is shown to enable control over the orientation of the chiral-nematic director across the topography of the template. Tuning the specific reflections and multiscaled fracture propagation is demonstrated for the microtemplated CNC films. The latter phenomenon contributed to enhancing the toughness of the material through a high tortuosity of fracture propagation in all (x, y, z) directions. The presented findings are expected to pave the way towards the incorporation of current research in cellular metamaterials with the research focusing on the generation of nanoscaled biomimetic constructs.
Created from Fastlane, Scopus look-up
Keywords: biomimetic; cellulose nanocrystals; conformability; hierarchical; tessellation